Dynamics of S. aureus Acquisition and Colonization in a Military Training Environment. (4th October 2017) - Schlett, Carey; Millar, Eugene; Elassal, Emad; Law, Natasha; Lyles, Demond; Hadley, Arile; Dowlen, Sidney; Hardge, David; Ellis, Michael; Bennett, Jason
Abstract: Background: Military trainees are known to be at increased risk for S. aureus colonization and skin and soft-tissue infections (SSTI). The longitudinal epidemiology of S. aureus colonization in this high-risk population is not well understood. Methods: A longitudinal cohort study of colonization and SSTI was conducted among Army trainees at Fort Benning, GA from 6/2015 to 11/2016. In total, four companies ( 200 trainees/company) were enrolled. Each subject was swabbed at four body sites at five time points (days 0, 14, 28, 56, and 90) to assess S. aureus colonization status. Specimens were processed by standard methods. S. aureus isolates underwent antibiotic susceptibility testing and molecular characterization, including PCR and pulsed-field gel electrophoresis. Results: Three-hundred forty-three subjects from two companies were enrolled in year one. At baseline, 70% were colonized with S. aureus in at least one site. Overall S. aureus /methicillin-resistant S. aureus (MRSA) colonization was highest in the oropharynx (60%/7%), followed by the nose (32%/3%), and the inguinal (11%/1%), and peri-anal (10%; 1%) regions. The prevalence of colonization in at least one body site was generally consistent throughout the training period: day 14 – 63%/9%; day 28 – 71%/10%; day 56 – 64%/11%; and day 90 – 62%/8%. MRSA were largely USA300 (54%) and USA800 (36%). The oropharynx was the most frequently colonized site (range, 29%-60%). Among those not nasally colonized at baseline, 54%/8% acquired S. aureus /MRSA in the nose by day 90. Sixty-nine (20%) subjects were persistently colonized in the nares (>80% cultures) throughout training while 108 (32%) subjects remained nasal colonization-negative at every time point. Conclusion: Military trainees experience a prolonged and intense exposure to S. aureus, as evidenced by a high colonization prevalence and colonization of multiple body sites over the duration of the training period. Effective decolonization strategies are needed to reduce the colonization burden of S. aureus, decrease transmission rates, and thereby reduce the risk of SSTI in the military training setting. Disclosures: All authors: No reported disclosures.